26.8k views
2 votes
What is tan(sin^-1(x/2))

with steps pls

User Felix Too
by
4.9k points

1 Answer

5 votes

Answer:


(x√(4-x^2))/(4-x^2)

Explanation:

Given:


\tan \left(\sin^(-1)\left((x)/(2)\right)\right)


\boxed{\begin{minipage}{5cm}\underline{Trigonometric Identity}\\\\$\tan(\arcsin(x))=(x)/(√(1-x^2))$\\ \end{minipage}}

Use the tan(arcsin(x)) trigonometric identity and replace x for (x/2):


\implies \tan\left(\arcsin \left((x)/(2)\right)\right)=\frac{\left((x)/(2)\right)}{\sqrt{1-\left((x)/(2)\right)^2}}

Simplify the denominator:


\implies \tan\left(\arcsin \left((x)/(2)\right)\right)=\frac{\left((x)/(2)\right)}{\sqrt{1-(x^2)/(4)}}


\implies \tan\left(\arcsin \left((x)/(2)\right)\right)=\frac{\left((x)/(2)\right)}{\sqrt{(4-x^2)/(4)}}


\implies \tan\left(\arcsin \left((x)/(2)\right)\right)=(\left((x)/(2)\right))/((√(4-x^2))/(√(4)))}


\implies \tan\left(\arcsin \left((x)/(2)\right)\right)=(\left((x)/(2)\right))/((√(4-x^2))/(2))}


\textsf{Apply the fraction rule}: \quad ((a)/(c))/((b)/(c))=(a)/(b)


\implies \tan\left(\arcsin \left((x)/(2)\right)\right)=(x)/(√(4-x^2))

Multiply the numerator and denominator by the denominator to eliminate the radical from the denominator:


\implies \tan\left(\arcsin \left((x)/(2)\right)\right)=(x)/(√(4-x^2)) \cdot (√(4-x^2))/(√(4-x^2))

Simplify:


\implies \tan\left(\arcsin \left((x)/(2)\right)\right)=(x√(4-x^2))/(4-x^2)

User Durga Mohan
by
4.1k points